LINGUISTIC REPRESENTATIONS OF PATRIOTISM: A COMPARATIVE ANALYSIS OF RUSSIAN, UZBEK, AND ENGLISH PROVERBS AND CULTURAL PERSPECTIVES (Intent Research Scientific Journal, 2024)
The findings in this article underscore the importance of studying linguistic expressions of cultural concepts to foster cross-cultural understanding. They also highlight how language evolves to reflect contemporary challenges, such as globalization and shifting societal priorities, while retaining its historical essence.